Blended Learning: Reflections on Teaching Experiences across the Pharmacy Education Continuum - Theresa J. Schindel; Christine A. Hughes; Cheryl A. Sadowski (MDPI AG, 2013)
Experiences with online learning in higher education have grown due to advancements in technology, technological savviness of students, changes in student expectations, and evolution of teaching approaches in higher education. Blended learning, the thoughtful fusion of face-to-face instruction with online learning, can enhance student learning and provide rewarding teaching experiences for faculty members. Pharmacy educators are beginning to employ blended learning across the continuum of professional education from entry-to-practice programs to continuing professional education programs. The objectives of this paper are to describe our early experiences with blended learning and how it has enhanced our teaching experiences. Possibilities for blended learning are considered as new curricula for pharmacy programs are developed at our institution.